MOTIVATION OF MEN AND WOMEN TO ADHANCE MUSCULATION PRACTICE (Fiep Bulletin - online, 2020)
ABSTRACT – The increased information about the benefits that exercise provides has influenced many individuals to change their habits, starting an active and healthy lifestyle. The present work aimed to investigate the factors that motivate men and women between 18 and 30 years to practice physical exercises in weight gyms, and the factors that influence the withdrawal. The research methodology used was based on a cross-sectional field study, with descriptive characteristics, in which the data were presented in a quantitative and qualitative way, using as support, scientific works that came to contribute to the theme. The results obtained in the present research show us that for both the male public (58%) and the female public (72%), the identified extrinsic motivation of regulation is the most sought for the practice of physical exercise, due to their characteristics. individual benefits (physical, emotional and behavioral). From the results of this study, we can conclude that the main factor in the search of young people in general, for bodybuilding exercises is based on extrinsic motivation, due to the individual interests that exercise provides. The factor related to the dropout of the studied population was the search for bodybuilding to avoid feelings of failure and to seek physical exercise for influence or to please the people around them. Thus, individuals do not have a daily motivation, resulting in the abandonment of the practice. Demotivation was not observed in the present study.